DIAGENESIS DAN BATUAN SUMBER BATUPASIR FORMASI LATI DI DAERAH BERAU, KALIMANTAN TIMUR, BERDASARKAN DATA PETROGRAFI - -, Sigit Maryanto (Bulletin of Scientific Contribution, 2009)
Petrography analysis result of twenty two sandstones of the Lati Formation were taken from Berau area, East Kalimantan showing that these rocks classified as litharenite, feldspathic litharenite, sublitharenite, feldspathic wacke, and lithic wacke witch are partially calcareous. Diagenetic processes visible on the petrographic analysis including as replacement, dolomitization, cementation, and compaction. Plotting result on the triangular diagrams showing that the provenance of the sandstones are dominated by granitic rocks initiated from tectonic setting of rifted continental margin and they have transported toward south-east.